University Education in Psychology in Argentina: Current Perspectives and Challenges from History - Klappenbach, Hugo Alberto; Universidad Nacional de San Luis (UNSL) Consejo Nacional de Investigaciones Cientificas y Tecnicas (CONICET) (Pontificia Universidad Javeriana, 2015)
This paper analyzes the beginnings of Psychology Education in Argentina and then focusing on the organization of undergraduate programs in the whole country. The aim is to carry out a complete updating information of all universities including psychology programs. Subsequently, the impact of the process of accreditation of undergraduate psychology programs is analyzed. Accreditation began in 2009 and it is not finish at all. On the other hand, graduate programs and organizations of psychology are also examined. It also confirms the professional and clinic bias that characterized Argentina psychology since the early 1960s.